Titiluri Tegger: Aktualisasi Tradisi, Refleksi Jati Diri dan Strategi Konservasi - Dina Fitria Hasanah; Sony Sukmawan (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The Tengger community coexists with cultural diversity. Titiluri presents to behold in maintaining cultural wealth. Focusing on what the ancestors have done, titiluri is a bridge in reducing the goodness that has existed since time immemorial. This study used a qualitative approach to the design of ethnography to describe titiluri role in maintaining society's culture Tengger. Through ethnographic design, a holistic description of folkloristic expression is embodied in expressions, speeches, symbolic behaviors that contain the philosophy of titiluri. Data were collected using observation and interviews. As a result, Titiluri is present in every aspect of the Tengger community. As a form of actualization of tradition, the titluri is shown to take place various traditional ceremonies until now as has been done by the ancestors. Besides, titiluri is present in the form of the Tengger community's identity, with inherent self-character, occupation, and dress characteristics. Titluri has the role of conserving the Tengger culture and becomes a principle in maintaining the nobility built by the ancestors so that it can save from the strong exposure of modernization.